2021
DOI: 10.48145/gopsbad.882760
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 SALGINININ TURİZM, ULAŞTIRMA VE YİYECEK&İÇECEK SEKTÖRLERİNE ETKİSİ: RALS ENGLE VE GRANGER EŞBÜTÜNLEŞME TESTİ

Abstract: The Covid-19 epidemic, which was declared as a pandemic by the World Health Organization on March 11, 2020, confronted the economies of countries with an unpredictable uncertainty and its impact was felt in all sectors deeply. The aim of this study is to put forward the impact of the Covid-19 epidemic on the tourism, transportation, and food & beverage sectors for the period of 17.03.2020-29.01.2021 in the Turkey sample. Accordingly, the effect of Turkey's daily deaths and cases caused by Covid-19 on the Bors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Although there are many theoretical or case studies (Akca, 2020;Kalkın, 2021;Keskin & Ercoşkun Yalçıner, 2021;Şen & Bütün, 2021) investigating the effects of COVID-19 on the aviation industry in the national literature, there are few empirical studies. The existence of a long-term relationship between the number of deaths caused by COVID-19 and BIST Tourism and BIST Transportation Indices was revealed by ARDL Boundary Test (Gümüş & Hacievliyagil, 2020) and RALS Engle and Granger Cointegration Test (Güngör et al, 2021). Deveci et al, (2022), revealed in their studies that COVID-19 affected the Turkish civil aviation industry to a large extent and it was reshaped with fewer carriers during the recovery phase.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although there are many theoretical or case studies (Akca, 2020;Kalkın, 2021;Keskin & Ercoşkun Yalçıner, 2021;Şen & Bütün, 2021) investigating the effects of COVID-19 on the aviation industry in the national literature, there are few empirical studies. The existence of a long-term relationship between the number of deaths caused by COVID-19 and BIST Tourism and BIST Transportation Indices was revealed by ARDL Boundary Test (Gümüş & Hacievliyagil, 2020) and RALS Engle and Granger Cointegration Test (Güngör et al, 2021). Deveci et al, (2022), revealed in their studies that COVID-19 affected the Turkish civil aviation industry to a large extent and it was reshaped with fewer carriers during the recovery phase.…”
Section: Literature Reviewmentioning
confidence: 99%